Upregulation of ppET-1/ETBR/eNOS mRNA Expression after Calcitriol Treatment in Chronic Kidney Diseases Model in Rats - Baskara, Anak Agung Ngurah Nata (Universiti Putra Malaysia Press, 2022)
Introduction: Myofibroblast formation in the interstitial area is the hallmark of chronic kidney disease (CKD). Endothelin signalling has been known to play role in physiology and pathophysiology in the kidney. Vitamin D has a reno-protective effect through inhibiting inflammation and fibrosis. However, the interaction between vitamin D and endothelin signalling in the CKD model has not been elucidated yet. Therefore, we aimed to check the difference impact of endothelin (ET) receptor in CKD. Methods: Sprague Dawley rats (3-months-old, 150-250grams) underwent 5/6 subtotal nephrectomy (SN) to induce CKD. Then, it was divided into 4 groups (each contains 6 rats): sham operation (SO), 5/6 subtotal nephrectomy (SN), calcitriol groups (0.01μg/100grBW/day (SN-D1), and 0.05μg/100grBW/day (SN-D2). Calcitriol was administered for 14 days after the surgery. The Sham Operation (SO) group was injected with NaCl. At the specified date, the rats were sacrificed and the kidneys were harvested. Fibrosis was quantified based on Sirius Red staining. Immunostaining was done for localizing fibroblast (PDGFRß). The mRNA expressions of prepro-ET-1, endothelin receptor A (ETAR), endothelin receptor B (ETBR), and endothelial nitrite oxide synthase (eNOS) were quantified using reverse-transcriptase PCR (RT-PCR). Results: The CKD promotes an elevation of prepro-ET-1, ETBR, and eNOS, and reduction of ETAR (p<0.05) mRNA expression compared to the SO group. Administration of calcitriol (SN-D1 and SN-D2) showed the vice versa effects. However, only SN-D2 group consistently showed statistically significant differences whenever compared to either SO or SN groups. Conclusion: Calcitriol might attenuate interstitial fibrosis in CKD model via ET-1/eNOS signalling. © 2022 UPM Press. All rights reserved.